MiR expression profiling at diagnosis predicts relapse in pediatric precursor B‐cell acute lymphoblastic leukemia. Issue 4 (19th December 2015) - Avigad, Smadar; Verly, Iedan RN; Lebel, Asaf; Kordi, Oshrit; Shichrur, Keren; Ohali, Anat; Hameiri‐Grossman, Michal; Kaspers, Gertjan JL; Cloos, Jacqueline; Fronkova, Eva; Trka, Jan; Luria, Drorit; et al.
Abstract : Our aim was to identify miRNAs that can predict risk of relapse in pediatric patients with acute lymphoblastic leukemia (ALL). Following high‐throughput miRNA expression analysis (48 samples), five miRs were selected for further confirmation performed by real time quantitative PCR on a cohort of precursor B‐cell ALL patients ( n = 138). The results were correlated with clinical parameters and outcome. Low expression of miR‐151‐5p, and miR‐451, and high expression of miR‐1290 or a combination of all three predicted inferior relapse free survival ( P = 0.007, 0.042, 0.025, and <0.0001, respectively). Cox regression analysis identified aberrant expression of the three miRs as an independent prognostic marker with a 10.5‐fold increased risk of relapse ( P = 0.041) in PCR‐MRD non‐high risk patients. Furthermore, following exclusion of patients harboring IKZF1 deletion, the aberrant expression of all three miRs could identify patients with a 24.5‐fold increased risk to relapse ( P < 0.0001). The prognostic relevance of the three miRNAs was evaluated in a non‐BFM treated precursor B‐cell ALL cohort ( n = 33). A significant correlation between an aberrant expression of at least one of the three miRs and poor outcome was maintained ( P < 0.0001). Our results identify an expression profile of miR‐151‐5p, miR‐451, and miR‐1290 as a novel biomarker for outcome in pediatric precursor B‐cell ALL patients, regardless of treatment protocol. The use of these markers may lead to improved risk stratification at diagnosis and allow early therapeutic interventions in an attempt to improve survival of high risk patients. © 2015 Wiley Periodicals, Inc.